2020
DOI: 10.1029/2020tc006305
|View full text |Cite
|
Sign up to set email alerts
|

An Exhumation Pulse From the Nascent Franciscan Subduction Zone (California, USA)

Abstract: We investigated a suite of metabasite blocks from serpentinite matrix and shale matrix mélanges of the California Coast Ranges. Our new data set consists of 40 Ar/ 39 Ar dates of amphibole and phengite and U-Pb dates of metamorphic zircon. Combined with published geochronology, including prograde Lu-Hf garnet ages from the same blocks, we can reconstruct the timing and time scales of prograde and retrograde metamorphism of individual blocks. In particular we find that exhumation from amphibole-eclogite facies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 107 publications
(227 reference statements)
1
13
0
Order By: Relevance
“…At later times, sediments are underplated and exhumed, complicating this comparison due to the greater buoyancy of sediments. Rutte et al (2020) propose a single exhumation event for high-grade blocks of the Franciscan Complex based on amphibolite and phengite Ar-Ar dating, perhaps consistent with a coherent underplating and exhumation model.…”
Section: Evolution Of the Franciscan Complex And Implications For Exhumation Modelssupporting
confidence: 52%
See 4 more Smart Citations
“…At later times, sediments are underplated and exhumed, complicating this comparison due to the greater buoyancy of sediments. Rutte et al (2020) propose a single exhumation event for high-grade blocks of the Franciscan Complex based on amphibolite and phengite Ar-Ar dating, perhaps consistent with a coherent underplating and exhumation model.…”
Section: Evolution Of the Franciscan Complex And Implications For Exhumation Modelssupporting
confidence: 52%
“…Protolith age constraints suggest the CRO formed between ∼172-162 Ma (e.g., Shervais et al 2005;Hopson et al 2008), and the oldest reported ages of metamorphism from Franciscan high-grade blocks, i.e., blocks with significantly higher metamorphic grade (blueschist, eclogite, and amphibolites facies) relative to the surrounding matrix, are ∼176 Ma (mean U-Pb age of metamorphic zircon inclusions in garnet, Mulcahy et al 2018). However, metamorphic zircon U-Pb ages from high-grade blocks are primarily younger ( ∼166-157 Ma), and ∼180 Ma ages (U-Pb zircon core) have been related to protolith basalt crystallization (Rutte et al 2020). The similar age of metamorphism of Franciscan high-grade blocks and formation of CRO magmatic and sedimentary rocks, suggests that subduction of the Franciscan complex occurred simultaneously with CRO formation (Anczkiewicz et al 2004), or that initiation of subduction of the Franciscan occurred slightly before CRO formation (Mulcahy et al 2018).…”
Section: Geologic History Of the Franciscan Complexmentioning
confidence: 99%
See 3 more Smart Citations